ANALISIS ELEMEN HINGGA BERBASIS ANSYS PADA SAMBUNGAN BAUT STRUKTUR COOLING TOWER - Rachmat Subagyo; Riyki Apriandi; Rakyan Permadi; Yanuar Iswahyudi; Renal Fajri (Scientific Journal of Mechanical Engineering Kinematika, 2025)
The cooling tower is a crucial component in industrial cooling systems, serving to dissipate heat from the working fluid. One of the main structural elements in a cooling tower is the bolt, which connects various components and plays a role in bearing mechanical loads. This study aims to perform numerical modeling and simulation of bolts within the cooling tower structure to understand the stress and deformation distribution under operational loads. The simulation was conducted using the finite element method based on ANSYS software, applying a pretension force of 200 Nm and a thermal load of 40 °C. The results show a maximum stress of 0.327 MPa at the contact area between the bolt head and the connecting plate, with a total deformation of 5.08×10⁻⁵ mm. The observed stress concentration indicates a potential risk of fatigue failure at the joint. This study provides valuable insights into the optimization of bolt design and material selection to enhance the cooling tower's resistance to operational loads.